Efficiency of Mining Investments: Models To Determine the Optimal Production Capacity in Mining Industry - Marius BULEARCĂ; Cornelia NEAGU; Daniel Fistung; Cristian SIMA (Communications of International Proceedings, 2021)
This paper intends to present different models for optimal production capacity in mining industry related to efficient mining investment process. After presenting a large literature review of the beginnings related to this issue, the article deals with models related to the calculation of optimal capacities by the variant method that may bring high efficiency of mining investments. In the paper we demonstrate that the size of a mining operation varies depending on the elements from which the production capacity results, therefore, increasing production capacity at a mine can be achieved mainly in two ways: increasing the number of elementary factors of production and changing the characteristics of the elementary factors of production. In doing this, the model presented in this paper starts from the determination of the production variants, passes through the calculation of the investments according to each variant, until the final calculation of the capital value or in other words until the calculation of the total net profits. And in the end, the paper discusses a model to determine of production capacities by a method of variants with the calculation of production costs on longwall mining systems emphasizing the most important ideas: calculation on variants, use of a discount factor, calculation of total net expenditures or profits during the exploitation of the entire reserve, and separate consideration of the investments made to the structure of the mine. Despite its shortcomings due to the large workload, the method is useful to apply because it ensures greater accuracy compared to other methods that are based on the analysis of statistical data.
Keywords: Longwall Mining System; Mining Industry; Mine Structure; Model; Production Cost; Reserves; Variant Method